2022
DOI: 10.4102/sajhivmed.v23i1.1428
|View full text |Cite
|
Sign up to set email alerts
|

Dolutegravir for second-line treatment: Programmatic implications of new evidence

Abstract: No abstract available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…1 , 4 However, based on results from the NADIA trial suggesting non-inferiority of recycling TDF instead of switching to AZT and the availability of TLD as a fixed dose combination, TDF/XTC/DTG is considered an easily implementable regimen in most LMICs. 7 Our findings have provided further assurance regarding these assertions with evidence from routine care. This finding is, therefore, also relevant to other resource-limited settings where resistance testing is not routinely done to guide the selection of NRTIs for second-line treatment.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…1 , 4 However, based on results from the NADIA trial suggesting non-inferiority of recycling TDF instead of switching to AZT and the availability of TLD as a fixed dose combination, TDF/XTC/DTG is considered an easily implementable regimen in most LMICs. 7 Our findings have provided further assurance regarding these assertions with evidence from routine care. This finding is, therefore, also relevant to other resource-limited settings where resistance testing is not routinely done to guide the selection of NRTIs for second-line treatment.…”
Section: Discussionsupporting
confidence: 56%
“…Some people with virological failure during first-line treatment might have been switched to TDF/3TC/DTG, either inadvertently as part of the transition to first-line DTG or by clinicians following preliminary evidence suggesting that TDF/3TC/DTG might be an effective second-line regimen. 7 As the rollout of DTG in low-income and middle-income countries (LMICs) continues, evidence on the effectiveness of different regimens in routine care settings is required to guide further rollout and confirm clinical trial findings. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that even with pre-existing nucleoside reverse transcriptase inhibitor (NRTI) resistance, switching to DTG, while maintaining the same NRTI backbone, achieves viral suppression rates of over 90%. 4 , 5 , 6 The ADVANCE trial demonstrated that DTG-containing regimens successfully re-suppress 95% of people experiencing viral load (VL) rebound above 1000 copies/mm 3 , without switching drugs. 7 These trials informed South Africa’s 2023 national HIV management guidelines, which recommend a very high threshold for resistance testing.…”
Section: Introductionmentioning
confidence: 99%
“…Some people with virologic failure during first-line treatment may have been switched to TDF/3TC/DTG, either inadvertently as part of the transition to first-line dolutegravir or by clinicians following preliminary evidence suggesting that TDF/3TC/DTG may be an effective second-line regimen. 7 As the rollout of DTG in low-and middle-income countries (LMICs) continues 8,9 , evidence on the effectiveness of different regimens in routine care settings is required to guide further rollout and confirm clinical trial findings. 7 Therefore, we aimed to evaluate the effectiveness of DTG plus emtricitabine/lamivudine (XTC) in combination with AZT or TDF versus the previously recommended regimen AZT/XTC/LPV/r for second-line treatment in routine care settings.…”
Section: Introductionmentioning
confidence: 99%